Understanding the Continuity of the Covid-19 Pandemic Via the Ministry's PASTI Appication - Nuraini Nuraini; Allif Syahputra Bania (Postgraduate, University of Mataram, 2026)
The important to understand Covid-19 as terminology is to build knowledge exchange and dissemination of scientific discoveries. This research is based on a qualitative-descriptive methodology. This research was conducted at Samudra University in the biology education study program. All respondents will be given a test to determine their understanding of Covid-19 terminology taken from data sources in the ministry's PASTI application. The test is a question related to the definition in the realm of translation of 10 terminologies that were randomly selected on the PASTI application. In general, this study yielded positive results, where respondents' understanding of the terminology related to Covid-19 via the PASTI application as an effort to preserve knowledge about Covid-19 was of high accuracy and the respondents' character was highly motivated to understand. The high accuracy rate, with 100% correct answers from 84 respondents, covered the terminology of Coronavirus, New Normal, Pandemic, and Work From Home. Thus, the research's overall contribution to science education and scientific literacy has a positive impact, helping to maintain accurate knowledge of COVID-19 and motivate the younger generation to understand.